2008
DOI: 10.1088/1475-7516/2008/08/031
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on local primordial non-Gaussianity from large scale structure

Abstract: Recent work has shown that the local non-Gaussianity parameter fNL induces a scale-dependent bias, whose amplitude is growing with scale. Here we first rederive this result within the context of peak-background split formalism and show that it only depends on the assumption of universality of mass function, assuming halo bias only depends on mass. We then use extended Press-Schechter formalism to argue that this assumption may be violated and the scale dependent bias will depend on other properties, such as me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
1,047
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(1,109 citation statements)
references
References 119 publications
57
1,047
3
2
Order By: Relevance
“…This is opened up the possibility to measure non-Gaussianities from the power spectrum of large scale structures. Analysis on the power spectra from current data in [41] have produced constraints comparable to the ones from CMB, while analysis of the bispectrum including the scale-dependent bias are expected to improve these limits even by about an order of magnitude [42]. Models of quasi single field inflation have a more general squeezed limit, so that the scale dependence of the bias goes as 1/k α with 1/2 ≤ α ≤ 2.…”
Section: Jhep10(2013)171mentioning
confidence: 99%
“…This is opened up the possibility to measure non-Gaussianities from the power spectrum of large scale structures. Analysis on the power spectra from current data in [41] have produced constraints comparable to the ones from CMB, while analysis of the bispectrum including the scale-dependent bias are expected to improve these limits even by about an order of magnitude [42]. Models of quasi single field inflation have a more general squeezed limit, so that the scale dependence of the bias goes as 1/k α with 1/2 ≤ α ≤ 2.…”
Section: Jhep10(2013)171mentioning
confidence: 99%
“…This excess power at large scale can be induced by primordial non-Gaussianity (see e.g. Matarrese & Verde 2008;Dalal et al 2008;Slosar et al 2008;Desjacques & Seljak 2010;Xia et al 2010) or exotic physics (Thomas et al 2010); however Samushia et al 2011 found that the redshift dependence of the excess power is different from what would be caused by non-Gaussianity, and Ross et al (2011) suggest that this is likely to be due to masking effects from stellar sources. After correcting for systematics, Ross et al (2012) found consistency at better than 2σ between the BOSS CMASS DR9 large-scale clustering data and the WMAP LCDM cosmological model.…”
Section: A4 Las Damas Mocksmentioning
confidence: 99%
“…Then, Dalal et al (2008) checked in numerical simulations that, in agreement with Eq. (2), the halo bias correction roughly grows as 1/k 2 at low k. This gives rise to a significant and specific signal that has already been used to constrain f NL (Slosar et al 2008). In this article, following a previous work devoted to the Gaussian case (Valageas 2009b), we revisit the derivations of the halo mass function and of the bias for primordial nonGaussianity.…”
Section: Introductionmentioning
confidence: 95%
“…High values of f NL can be obtained, for instance, from multifield inflation (Bartolo et al 2002;Lyth et al 2003), self-interactions (Falk et al 1993), tachyonic preheating in hybrid inflation (Barnaby & Cline 2006), or ghost inflation (Arkani-Hamed et al 2004). Current limits are −9 < f NL < 111 from CMB (Komatsu et al 2009) and −29 < f NL < 70 from large-scale structures (Slosar et al 2008). The effects of primordial non-Gaussianity on large-scale structures can be seen, for instance, through the mass function of virialized halos, especially in the high-mass tail as the steep falloff magnifies the sensitivity to initial conditions (Lucchin & Matarrese 1988;Colafrancesco et al 1989;Grossi et al 2007;Maggiore & Riotto 2009).…”
Section: Introductionmentioning
confidence: 99%